Optimalisasi metode uji perkecambahan dan media tanam pada perkecambahan biji anuma (Artemisia annua L.) - Murtiwulandari; Endang Pudjihartati (Jurnal Ilmiah Pertanian, 2022)
Annual wormwood (Artemisia annua L.) is a traditional Chinese medicinal plant belonging to a group of tiny seeds. The small size of the seeds requires the appropriate germination test method and medium. This study aimed to find the best seed germination test methods and growing media; also the best combination of methods and germination media for determining the viability and vigor of A. annua seeds. The experiment used a factorial randomized block design repeated three times, given two treatments: the type of method and the media. The methods used were the top-of-the-paper test (UDK), the between-paper test (UAK), and the rolled paper and erected-in-plastic test (UKDDdp). The media used included garden soil (control), straw paper, filter paper, CD paper, tissue towel, and soft tissue, so there were 15 treatment combinations and one control. Data analysis used a SAS and DMRT follow-up test with a 5% significance level. The results showed that of the observation variables for germination percentage (DB) and growth speed (KCT), the UDK test method became the best method. As a result of the main effect of media, filter paper became the best medium, while straw paper became the lowest after soil. In the seed viability testing, there was no interaction for a combination of methods and media, but only the UDK combination of filter paper reached DB=80%. Meanwhile, there was an interaction in the vigor test of the simultaneous growth (KST), and the best combination was to use the UDK method with towel tissue and soft tissue.